Implementasi Kebijakan Kota Layak Anak Di Kabupaten Gorontalo: Perspektif Perlindungan Anak Dan Perempuan - Arsjad, Muh Fachri; Tabo, Sarfan; Nuna, Muten S; Usman, Masjrul Janto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
The Government of Indonesia has initiated the Child-Friendly City (Kota Layak Anak/KLA) program to create a conducive environment for the optimal growth and development of children. This program is based on the Convention on the Rights of the Child and aims to ensure protection from violence, discrimination, and exploitation. Gorontalo Regency is one of the regions that has adopted this policy through Regional Regulation Number 1 of 2020 concerning the Child-Friendly Regency. However, its implementation still faces several challenges, such as limited budget, lack of professional personnel, and low public awareness of children's and women's rights. This study aims to analyze the implementation of the KLA policy in Gorontalo Regency from the perspective of child and women protection, as well as to identify the supporting and inhibiting factors of its implementation. The research method uses a qualitative approach through interviews, observations, and documentation, with informants from the Department of Women’s Empowerment and Child Protection (DP3A), the Social Service, and community leaders. The analysis refers to George C. Edwards III’s policy implementation theory, which includes communication, resources, implementer disposition, and bureaucratic structure. The research results show that communication and public outreach efforts have been conducted but are not yet widespread. Budget and human resource availability remain limited, while the implementers show commitment despite constrained capacities. The bureaucratic structure has been established, but coordination among government agencies (OPD) needs to be strengthened. Therefore, there is a need to increase funding, involve professional personnel, and reinforce cross-sector collaboration and socialization. In conclusion, the commitment of the local government is relatively strong, but technical and social challenges still hinder the optimal implementation of the KLA program. Comprehensive improvements are required to realize the vision of Gorontalo Regency as a child-friendly region